2012
DOI: 10.1093/cid/cis327
|View full text |Cite|
|
Sign up to set email alerts
|

Preliminary Assessment of the Efficacy of a T-Cell–Based Influenza Vaccine, MVA-NP+M1, in Humans

Abstract: A single vaccination with MVA-NP+M1 boosts T-cell responses to conserved influenza antigens in humans. Protection against influenza disease and virus shedding was demonstrated in an influenza virus challenge study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
217
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 229 publications
(225 citation statements)
references
References 14 publications
2
217
0
Order By: Relevance
“…First, we recognize that it is difficult to separate the roles of ADCC and T cells in controlling H1N1pdm replication, although recent experiments with humans suggest a limited role for T cell immunity (53). Future experiments using passive antibody transfer, adoptive T cell transfer, and antibody- mediated depletion of lymphocyte subsets will help to delineate the distinct roles of these cells in mediating cross-protection.…”
Section: Discussionmentioning
confidence: 99%
“…First, we recognize that it is difficult to separate the roles of ADCC and T cells in controlling H1N1pdm replication, although recent experiments with humans suggest a limited role for T cell immunity (53). Future experiments using passive antibody transfer, adoptive T cell transfer, and antibody- mediated depletion of lymphocyte subsets will help to delineate the distinct roles of these cells in mediating cross-protection.…”
Section: Discussionmentioning
confidence: 99%
“…Several candidate universal influenza vaccines are in various stages of development (29,34,(53)(54)(55)(56). Those that aim at the induction of cross-protective T cell responses especially hold promise, as it has been shown in numerous animal models that the induction of virus-specific T cell responses affords protection against challenge infection (12,57).…”
Section: Discussionmentioning
confidence: 99%
“…IIa vaccination and influenza challenge study, MVA-NP+M1 additionally demonstrated clinical efficacy in healthy adult volunteers [10]. A coadministration regimen could have the advantage of simultaneously inducing cell-mediated and humoral immunity.…”
Section: Indicated That Preexisting Cd4mentioning
confidence: 96%